The Domination of The Salafi Movement in West Sumatra: Framing Analysis on Surau TV Channel - Anjali Sabna (Universitas Islam Negeri Imam Bonjol Padang, 2022)
This study aims to analyze the social discourse contained in salafi da'wah content on the Surau TV Youtube channel. By looking at the content distributed by salafi groups in West Sumatra, this study uses qualitative research methods with data collection techniques using digital data and literature studies. Furthermore, the data analysis in this study is using Robert D. Benford and David Snow framing analysis which includes; diagnostic, prognostic and motivational. This study finds that there are three social discourses contained in Surau TV content including: addiction to technology, usury transactions, and interactions between Muslims and non-Muslims. Surau TV diagnoses problems in implementing Islamic law, starting from the technological aspect, Socio-cultural and religious attitudes are issues that need to be considered in upholding Islamic law and forming harmonious relations between religions. In its prognostic strategy, Surau TV creates content that incorporates the application of Islamic law in everyday life. In addition, the motivational strategy, Surau TV invites for tips to apply Islamic law in daily life in order to create a generation that is in accordance with Islamic law.Studi ini bertujuan menganalisa wacana sosial yang terdapat dalam konten dakwah salafi di channel Youtube Surau TV. Dengan melihat konten-konten yang disebarkan oleh kelompok salafi di Sumatera Barat, studi ini menggunakan metode penelitian kualitatif dengan teknik pengumpulan data menggunakan data-data digital dan studi literatur. Selanjutnya analisis data dalam penelitian ini yakni menggunakan analisis framing Robert D. Benford dan David Snow yang meliputi; diagnosis, prognosis dan motivasional. Studi ini menemukan bahwa terdapat tiga wacana sosial yang terdapat dalam konten Surau TV diantaranya: kecanduan dalam berteknologi, transaksi riba, dan interaksi antara muslim dan non muslim. Surau TV mendiagnosis, permasalahan dalam menerapkan syariat Islam mulai dari aspek teknologi, sosial budaya dan sikap dalam beragama merupakan permasalahan yang perlu diperhatikan dalam menegakkan syariat Islam dan membentuk hubungan yang harmonis antar agama. Dalam strategi prognosisnya, Surau TV menciptakan konten-konten yang berunsur penerapan syariat Islam tersebut dalam kehidupan sehari-hari. Disamping itu, strategi motivasionalnya, Surau TV mengajak untuk kiat menerapkan syariat Islam dalam kehidupan sehari-hari demi menciptakan generasi yang sesuai dengan syariat Islam.